2021
DOI: 10.47743/saeb-2021-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Economic Growth on Employment in GCC Countries

Abstract: The objective of this research is to analyze the employment intensity of growth in six Gulf Cooperation Council countries between 1970 and 2017. To this end, a two-step econometric methodology is proposed. First, we estimate the time-varying employment intensity of growth using the time-varying parameters model based on the Kalman filter. Second, we identify the short and long-run determinants of the obtained employment intensity of growth using the Pooled Mean Group estimator. The analysis uncovers that elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The literature analysing the impact of economic growth on employment confirms the different responsiveness of employment to output growth across countries, groups of countries and over time (Burggraeve, 2015;El-Hamadi et al, 2017;Ben-Salha & Zmami, 2021). The main findings implicate the higher employment-output elasticity in more developed regions compared with less developed and increasing (Adegboye et al, 2019) or decreasing (Ghazali & Mouelhi, 2018) employment sensitivity to output growth over time.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The literature analysing the impact of economic growth on employment confirms the different responsiveness of employment to output growth across countries, groups of countries and over time (Burggraeve, 2015;El-Hamadi et al, 2017;Ben-Salha & Zmami, 2021). The main findings implicate the higher employment-output elasticity in more developed regions compared with less developed and increasing (Adegboye et al, 2019) or decreasing (Ghazali & Mouelhi, 2018) employment sensitivity to output growth over time.…”
Section: Introductionmentioning
confidence: 88%
“…The main findings implicate the higher employment-output elasticity in more developed regions compared with less developed and increasing (Adegboye et al, 2019) or decreasing (Ghazali & Mouelhi, 2018) employment sensitivity to output growth over time. Part of the literature concentrates on employment intensity of growth at the sectoral level: sectoral employment intensity of sectoral value-added (Guisan & Exposito, 2017;Thuku et al, 2019;Zaki et al, 2020), sectoral employment intensity of overall economic growth (Ghazali & Mouelhi, 2018;Gelfer, 2020), and total employment intensity of sectoral value added (Arias-Vazquez et al, 2012;Ben-Salha & Zmami, 2021). Regardless of the analysis type, in the majority of the research, the service sector was found as the most job-intensive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of studies on the economic growth-employment nexus (Seyfried 2007(Seyfried , 2014Herman 2011;Furceri et al 2012;Hartwig 2014;Richter and Witkowski 2014;Ezzahidi and El Alaoui 2014;Burggraeve et al 2015;Dahal and Rai 2019;Thuku et al 2019;Adegboye et al 2019;Mkhize 2019;Ben-Salha and Zmami 2021;Mihajlović and Marjanović 2021; usually show the positive but heterogeneous impact of economic growth on employment. Authors have analysed the output-employment elasticities in individual countries (Seyfried 2007(Seyfried , 2014Hartwig 2014;Ezzahidi and El Alaoui 2014;Burggraeve et al 2015;Dahal and Rai 2019;Thuku et al 2019) or regions (Furceri et al 2012;Richter and Witkowski 2014;Adegboye et al 2019;Mkhize 2019;Ben-Salha and Zmami 2021;Mihajlović and Marjanović 2021) but there is a scarcity of research conducted in the European Union as a whole (Herman 2011;Richter and Witkowski 2014;Burggraeve et al 2015). Since European Union countries follow rather different employment strategies and targets, it is important to know whether economic growth in the European Union as a whole leads to employment growth or whether the growth not connected to jobs.…”
Section: Introductionmentioning
confidence: 99%
“…Authors have also determined the factors influencing heterogeneity of the outputemployment relationship: specific economic characteristics of each country (Pattanaik and Nayak 2014;Slimane 2015;Burggraeve et al 2015;El-Hamadi et al 2017;Ali et al 2018;Dahal and Rai 2019;Thuku et al 2019;Mkhize 2019;Ben-Salha and Zmami 2021), institutional (Kapsos 2006;Furceri et al 2012;Richter and Witkowski 2014;Ali et al 2018;Ben-Salha and Zmami 2021), and demographic characteristics (Furceri et al 2012;Anderson and Braunstein 2013;Pattanaik and Nayak 2014;Slimane 2015;Anderson 2016;Ben-Salha and Zmami 2021). Scientific literature emphasises that employment reaction to economic growth could vary across gender (Kapsos 2006;Anderson and Braunstein 2013;Anderson 2016;Adegboye et al 2019) or age (Kapsos 2006;Adegboye et al 2019), with most estimations indicating the higher responsiveness of employment to economic growth for females compared to males, and lower for youth compared to total male and female outputemployment elasticities.…”
Section: Introductionmentioning
confidence: 99%